Low adiponectin is associated with diastolic dysfunction in women: A cross-sectional study from the Tromsø Study - Norvik, Jon Viljar; Schirmer, Henrik; Ytrehus, Kirsti; Jenssen, Trond Geir; Zykova, Svetlana; Eggen, Anne Elise; Eriksen, Bjørn Odvar; Solbu, Marit Dahl (BMC Cardiovascular Disorders, 2017)
Source at https://doi.org/10.1186/s12872-017-0509-2 Background: Heart failure with preserved ejection fraction is closely associated with diastolic dysfunction and related to obesity and female sex. We investigated whether adiponectin, an adipocyte-secreted protein hormone with cardioprotective effects, was associated with indices of diastolic dysfunction, and whether the association was sex dependent. Methods: We conducted a cross-sectional study on 1165 women and 896 men without diabetes. We stratified the multivariable adjusted logistic regression analyses and the fractional polynomi al regression analyses according to sex, with echocardiographic markers of diastolic dysfunction as dependent variables, and adiponectin as the independent variable of interest. Results: Decreased adiponectin was associated with higher odds of average tissue Doppler e ’ < 9 in women (odds ratio [OR] 1.17 per 1 μ g/mL adiponectin decrease, 95% confidence interval [CI] 1.04 – 1.30), but not in men (p for interaction with sex 0.04). Women, but not men, had higher odds of E/e ’ ratio ≥ 8 with lower adiponectin (OR 1.12 per 1 μ g/mL adiponectin decrease, 95% CI 1.02 – 1.24, p for interaction with sex 0.04). Adiponectin in the lower sex-specific tertile was associated with increased odds of concentric left ventricular hypertrophy in women (OR 2.44, 95% CI 1.03 – 5.77), but with decreased odds in men (OR 0.32, 95% CI 0.11 – 0.88, p for interaction with sex 0.002), and decreased odds of eccentric hypertrophy in men only (OR 0.53, 95% CI 0.33 – 0.88, p for interaction with sex 0.02). Adiponectin in the lower sex-specific tertile was associated with moderately enlarged left atria in women only (OR 1.43, 95% CI 1.01 – 2.03, p for interaction with sex 0.04). Finally, adiponectin had a non-linear relationship with left ventricular mass in women only, with exponentially increasing left ventricular mass with lower adiponectin levels (p for interaction with sex 0.01). Conclusions: Low adiponectin was associated with higher odds of indices ...